DEVELOPMENT OF LEARNING GUIDANCE AND COUNSELING - Rifqi Muhammad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This paper aims to describe the development of learning guidance and counseling. The development of tutoring for counselees is carried out with the following efforts, namely: Introduction of Psychological Learning Difficulties; Disclosure of Counselees' Learning Problems or Difficulties; Counseling Learning Difficulty Solving Assistance; Increasing Counselee's Learning Motivation; Development of Good Study Attitudes and Habits; Improving the Counselor's Learning Skills; and Service Delivery Improvement Program